Role of ferritin, vitamin D, and thyroid dysfunction in telogen effluvium among the hospital population in Western Saudi Arabia: a case-control study - Salma S Mohammed; Mohammad I Fatani; Abdulmajeed S Khan (Wolters Kluwer Medknow Publications, 2021)
Background and aim This case-control study was conducted to evaluate serum ferritin, vitamin D, and thyroid functions in patients with telogen effluvium (TE) in comparison with controls and to find if they can be used as diagnostic biomarkers of TE. Patients and methods A retrospective matched case-control study was performed using data from Hera Hospital database, Makkah, Saudi Arabia. The case records of 100 women diagnosed with TE and treated in the dermatology outpatient clinic were analyzed retrospectively. To obtain appropriate controls, records were searched for age-matched and sex-matched women who came to the hospital for a condition other than TE during the same period. Results The mean levels of patients' serum ferritin and vitamin D were significantly lower than those of the controls. With respect to thyroid function tests, the mean levels of thyroid-stimulating hormone, thyroxine, and triiodothyronine showed no statistically significant differences between patients and controls. Although nonsignificant, 7% of patients with TE had laboratory evidence of hypothyroidism compared with 2% of controls, and 16% had subclinical hypothyroidism compared with 10% of controls, suggesting a role of thyroid dysfunction in TE. Conclusions Low serum ferritin, vitamin D deficiency, and thyroid dysfunction could be the risk factors for TE and can be used as diagnostic biomarkers of TE; hence, treating such patients with iron, vitamin D, and correction of thyroid dysfunction would be valuable. Prospective clinical studies with a larger number of participants are required to further address the risk factors for TE.